Relationship Between Knowledge Level And Menstrual Genital Hygiene Among UMI Medical Students - Andi Ifthita Audy Maharani; Lisa Yuniati; Hanna Aulia Namirah; M. Hamsah; Gina Isni Djanuaresty Iskandar (Fakultas Kedokteran Universitas Malikussaleh, 2026)
Menstruation is a physiological process that may increase the risk of reproductive tract infections if personal hygiene is not properly maintained. Genital hygiene behavior during menstruation plays an important role in maintaining reproductive health; however, many women still have inadequate hygiene practices, one of which is influenced by limited knowledge. Therefore, this study aimed to determine the relationship between knowledge level and genital hygiene behavior during menstruation, as well as differences in knowledge level and genital hygiene behavior among female students of the Faculty of Medicine and the Faculty of Economics and Business, Universitas Muslim Indonesia (UMI), class of 2023. This study used a quantitative design with an observational analytic method and a cross-sectional approach. The results showed that most female students from both faculties had good knowledge levels and good genital hygiene behavior during menstruation. Statistical analysis revealed a significant relationship between knowledge level and genital hygiene behavior in both faculties (p = 0.001). Significant differences were also found in knowledge level between medical and non-medical students, with medical students having higher knowledge levels (p = 0.004). In addition, genital hygiene behavior during menstruation was significantly better among medical students compared to students from the Faculty of Economics and Business (p = 0.023). These findings indicate the importance of strengthening structured and equitable reproductive health education across all faculties to improve genital hygiene behavior during menstruation among female students.